2005
DOI: 10.1126/science.1113150
|View full text |Cite
|
Sign up to set email alerts
|

Inositol Hexakisphosphate Is Bound in the ADAR2 Core and Required for RNA Editing

Abstract: We report the crystal structure of the catalytic domain of human ADAR2, an RNA editing enzyme, at 1.7 angstrom resolution. The structure reveals a zinc ion in the active site and suggests how the substrate adenosine is recognized. Unexpectedly, inositol hexakisphosphate (IP 6 ) is buried within the enzyme core, contributing to the protein fold. Although there are no reports that adenosine deaminases that act on RNA (ADARs) require a cofactor, we show that IP 6 is required for activity. Amino acids that coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
496
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 386 publications
(509 citation statements)
references
References 40 publications
11
496
1
1
Order By: Relevance
“…The C-terminal region of ADAR contains amino-acid residues that are conserved in several cytidine deaminases and are predicted to participate in the formation of the catalytic centre of ADAR 30,38 . The crystal structure of the catalytic domain of human ADAR2 shows that His394, Glu396 and two Cys residues, Cys451 and Cys516, of ADAR2 are indeed involved in the coordination of a zinc atom and the formation of the catalytic centre 39 . Most surprisingly, however, the structural studies also revealed the presence of inositol hexakisphosphate (IP 6 ) buried in the enzyme core, but located very close to the catalytic centre.…”
Section: Domain Structure Of Adarsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C-terminal region of ADAR contains amino-acid residues that are conserved in several cytidine deaminases and are predicted to participate in the formation of the catalytic centre of ADAR 30,38 . The crystal structure of the catalytic domain of human ADAR2 shows that His394, Glu396 and two Cys residues, Cys451 and Cys516, of ADAR2 are indeed involved in the coordination of a zinc atom and the formation of the catalytic centre 39 . Most surprisingly, however, the structural studies also revealed the presence of inositol hexakisphosphate (IP 6 ) buried in the enzyme core, but located very close to the catalytic centre.…”
Section: Domain Structure Of Adarsmentioning
confidence: 99%
“…Most surprisingly, however, the structural studies also revealed the presence of inositol hexakisphosphate (IP 6 ) buried in the enzyme core, but located very close to the catalytic centre. The IP 6 molecule could have a crucial role during the deamination reaction 39 .…”
Section: Domain Structure Of Adarsmentioning
confidence: 99%
“…The RNA-binding domain consists of one to three double-stranded RNA-binding motifs (dsRBM). The catalytic domain consists of a deaminase motif that resembles Escherichia coli cytidine deaminase and binds zinc, as well as a motif that coordinates the small molecule myo-inositol hexakisphosphate (IP 6 , Maas et al, 2003;Macbeth et al, 2005). In addition, human and Xenopus ADAR1 contain two Z-DNA-binding motifs N-terminal to their three dsRBMs (Maas et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…ADAR2 displays a modular organization with two tandem dsRNA-binding motifs (dsRBMs) connected by a flexible linker and a conserved adenosine deaminase domain toward the carboxy terminus, for which the structures have recently been determined (Macbeth et al, 2005;Stefl et al, 2006). The dsRBM is a highly conserved 65-75 amino acid (aa) domain, present in many eukaryotic proteins with diverse cellular functions, that forms an ␣1-␤1-␤2-␤3-␣2 topology in which the two ␣-helices are packed along a face of a three-stranded antiparallel ␤-sheet, with most of the potential RNA-binding residues exposed on one surface (FierroMonti and Mathews, 2000;Tian et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The most extensively studied substrates of Ato-I conversion are transcripts encoding ionotropic glutamate receptor (GluR) subunits and the 2C-subtype of the serotonin receptor (5-HT 2C R), in which editing leads to nonsynonymous codon changes that generate channels with altered electrophysiologic and ion permeation properties (Seeburg and Hartner, 2003) and receptors with decreased G protein-coupling efficiency (Burns et al, 1997;Niswender et al, 1999;Berg et al, 2001). A-to-I modifications have also been described in nontranslated RNAs and noncoding regions of mRNA transcripts, suggesting that such RNA modifications affect other aspects of RNA function, including splicing, translation efficiency, nuclear retention, and transcript stability (Rueter et al, 1999;Athanasiadis et al, 2004;Blow et al, 2004;Kim et al, 2004;Levanon et al, 2004;DeCerbo and Carmichael, 2005;Prasanth et al, 2005).ADAR2 displays a modular organization with two tandem dsRNA-binding motifs (dsRBMs) connected by a flexible linker and a conserved adenosine deaminase domain toward the carboxy terminus, for which the structures have recently been determined (Macbeth et al, 2005;Stefl et al, 2006). The dsRBM is a highly conserved 65-75 amino acid (aa) domain, present in many eukaryotic proteins with diverse cellular functions, that forms an ␣1-␤1-␤2-␤3-␣2 topology in which the two ␣-helices are packed along a face of a three-stranded antiparallel ␤-sheet, with most of the potential RNA-binding residues exposed on one surface (FierroMonti and Mathews, 2000;Tian et al, 2004).…”
mentioning
confidence: 99%